2008
DOI: 10.1002/jbm.b.31258
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite fiber material with BMP‐2 gene induces ectopic bone formation

Abstract: Collagen containing bone morphogenetic protein-2 (BMP-2) expression vector, which is called "gene-activated matrix," promotes bone regeneration when transplanted to the bone defect. We speculated that hydroxyapatite fiber (HF) would be an ideal matrix for "gene-activated matrix" especially for bone regeneration, because it is oseteoconductive and has high affinity to DNA. The purpose of this study is to clarify whether HF containing BMP-2 expression vector induces ectopic bone formation. We prepared HF contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…In this study, we showed that HAF can serve as a substance carrier by demonstrating the stable release of simvastatin from HAF/simvastatin compound materials. This is in agreement with the report by Oda et al [14], who suggested HAF as a potential component of a drug-delivery system based on its biocompatibility, biode-gradability, and cotton-like fibrous 3D structure. Importantly, the effects of HAF in bone formation have been demonstrated by using the rabbit cranium chamber model [12] and the post-extraction tooth socket model [13].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we showed that HAF can serve as a substance carrier by demonstrating the stable release of simvastatin from HAF/simvastatin compound materials. This is in agreement with the report by Oda et al [14], who suggested HAF as a potential component of a drug-delivery system based on its biocompatibility, biode-gradability, and cotton-like fibrous 3D structure. Importantly, the effects of HAF in bone formation have been demonstrated by using the rabbit cranium chamber model [12] and the post-extraction tooth socket model [13].…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that our highest dose (0.75 mg) might not have been high enough to cause inflammatory reaction. Another curious effect of simvastatin is ectopic bone formation [14]. In our study model, in which the chamber was covered by periosteum, some mesenchymal cells could have had the chance to enter from the top of the chamber.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…For instance, the synthesis of a tissue-engineered bone construct usually requires a 6-12 week culture and seeding period. [9][10][11] These long construction times are not oncologically safe for rapidly growing malignancies. Similarly, long culture periods are a significant drawback to the use of tissueengineered constructs for traumatic defects, as they would require prolonged open wound care and convalescence.…”
Section: Introductionmentioning
confidence: 99%
“…(64) A lower (10 µg) plasmid dose was also effective but required 12 weeks to show radiopaque tissue. HA may be an optimal scaffold as the scaffold itself induced formation of calcified tissue in this study.…”
Section: Nell1mentioning
confidence: 99%